Clinical evaluation of a jejunojejunal end‐to‐end anastomosis with skin staples with or without coverage by a mesenteric flap. (26th May 2015) - Gandini, M.; Giusto, G.
Summary: This study describes a novel end‐to‐end‐jejunojejunal‐anastomotic technique using skin staples following resection of compromised small intestine. Five horses were referred with colic and underwent exploratory laparotomy, resection and anastomosis. No long‐term complications were recorded at 12 months. This safe and effective technique may be used in equine gastrointestinal surgery.